2017
DOI: 10.2139/ssrn.2951699
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Corporate Governance and Tax Avoidance Evidence from Germany Using a Regression Discontinuity Design

Abstract: The relationship between corporate governance and tax avoidance-evidence from Germany using a regression discontinuity design arqus Discussion Paper, No. 218

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…So, if the firm is audited by a BIG4, it is less likely to adopt aggressive tax strategies. This finding is similar with those of Kiesewetter and Manthey (2017), Pilos (2017) and Gaaya et al (2017) and then we support our second hypothesis. Indeed, audit quality is considered one of the most effective governance mechanisms because it protects users against the opportunistic and fraudulent actions of managers.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…So, if the firm is audited by a BIG4, it is less likely to adopt aggressive tax strategies. This finding is similar with those of Kiesewetter and Manthey (2017), Pilos (2017) and Gaaya et al (2017) and then we support our second hypothesis. Indeed, audit quality is considered one of the most effective governance mechanisms because it protects users against the opportunistic and fraudulent actions of managers.…”
Section: Resultssupporting
confidence: 92%
“…In this context, Armstrong et al (2015) confirmed thatmanager can abuse and engage in tax avoidance activities in low-governed firm. Likewise, Kiesewetter and Manthey (2017) and Pilos (2017) found that good governance structure reduces level of tax ovoidance.…”
Section: Moderating Effect Of Audit Qualitymentioning
confidence: 98%
“…Indeed, the variables size of the board of directors, the independence of its members and gender diversity have a positive and statistically insignificant impact on the probability of the presence of tax risk in Tunisian listed companies. On the other hand, the direction duality variable registers a positive and statistically significant correlation with the variable to be explained (Kiesewetter and Manthey, 2017).…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 92%
“…Further, in order to adequately examine the executive compensationtax aggressiveness relationship, several variables were considered to control for individual company characteristics following an extant literature review (e.g. Campbell et al, 2017;Halioui et al, 2016;Kiesewetter and Manthey, 2018;Richardson et al, 2013). These included size, profitability, leverage, capital intensity, growth, foreign activity, R&D intensity, operating volatility and industry as well as year indicators (CONTROLS).…”
Section: Corporate Tax Aggressiveness In Indiamentioning
confidence: 99%